1993
DOI: 10.3109/00048679309072117
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Psychiatric Diagnoses in New Zealand Psychiatric Hospitals

Abstract: This study examines the stability over a five year follow-up of first admission psychiatric diagnoses assigned in New Zealand psychiatric hospitals in 1980 and 1981. Diagnostic stability is a measure of the degree to which psychiatric diagnoses remained unchanged at a later hospital admission. Reasonably high levels of stability were found for the initial diagnoses of substance abuse disorders (86% stable), anorexia nervosa (70%), schizophrenia (67%), and affective disorder (67%). Poor levels of stability were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Schizophrenia is particularly difficult to diagnose as there are several conditions that may mimic it and the pattern of psychotic symptoms tends to be relatively unstable early in the course of the illness. [26][27][28] For all these reasons, GPs should remain wary of a diagnosis of schizophrenia, even when long "established". If response to treatment is poor or the patient seems particularly sensitive to the adverse effects of treatment, a reappraisal of the diagnosis, including specialist reassessment, should be considered.…”
Section: Diagnosismentioning
confidence: 99%
“…Schizophrenia is particularly difficult to diagnose as there are several conditions that may mimic it and the pattern of psychotic symptoms tends to be relatively unstable early in the course of the illness. [26][27][28] For all these reasons, GPs should remain wary of a diagnosis of schizophrenia, even when long "established". If response to treatment is poor or the patient seems particularly sensitive to the adverse effects of treatment, a reappraisal of the diagnosis, including specialist reassessment, should be considered.…”
Section: Diagnosismentioning
confidence: 99%
“…Hospitalised patients show a stability around 70% for the diagnosis of M D D ; 67% after 5 years' follow up [23], 74% after 6 years [24], between 67 and 76% after 7 years depending on diagnostic criteria [25], The stability of diagnosis o f bipolar depres sion is higher than that o f unipolar depression: 76 vs. 44% after 7 years [26], and 79 vs. 66% after 25 years [27], A differentiation o f the bipolar diagnosis into bipolar 1 and II showed that the latter are more instable (34 vs. 66%) [28]. In contrast, the Zürich study showed that the diagnosis of M D D remained consistent only in 15% o f a non-hospitaliscd sample [taken from table 10 in 29], When considering that our SA D patients were nearly all unipolar (stability o f this diagnosis between 44 and 66% [26,27]), and that nearly all were outpatients (stability of diagnosis M D D in an ambulatory population of 15% [29]), our estimate o f diagnosis stability between 70 and 90% is a remarkably high one.…”
Section: Discussionmentioning
confidence: 99%
“…10,23 Stability refers to the proportion of diagnoses that remain unchanged over time according to multiple, successive evaluations. For a diagnosis to be stable, it has to be reliable in the fi rst place.…”
Section: Validity Of the Psychiatric Diagnosismentioning
confidence: 99%
“…10,11 Conversely, methodological artifacts in the diagnostic process, such as variability in information sources, poor or absent use of reliable diagnostic classifi cation systems and standardized diagnostic instruments, and lack of professional experience all might lead to mistakes in the initial diagnosis. 23 Current diagnostic classifi cation systems in psychiatry, consisting of the DSM, published by the American Psychiatric Association, 8 and of Section 5 of the International Classifi cation of Diseases (ICD-10), published by the World Health Organization, 24 have signifi cantly contributed to enhance the stability of the psychiatric diagnosis performed during a fi rst psychotic episode or in the fi rst psychiatric hospitalization. In general, the diagnoses of schizophrenia and mood disorders -especially bipolar disorder -performed in accordance with the two classifi cation systems for patients in a fi rst psychotic episode proved to have adequate positive predictive values.…”
Section: Validity Of the Psychiatric Diagnosismentioning
confidence: 99%